Temporary vascular access complications and its impact on quality of life among hemodialysis patients - Pa, Norummi Amirah Che (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Temporary Venous Access (TVA) is commonly used for patients with chronic renal failure when the vascular access is immature or dysfunction and patients who need for acute hemodialysis (HD) treatment. The objective of this study is to determine the occurrence of TVA complication, the types and its impact on quality of life among HD patients. A cross sectional survey was conducted within two months period on 52 patients HD patients with TVA who underwent hemodialysis treatment in Hemodialysis Unit at Hospital USM. Altogether, there were 19 males and 33 female respondents involved in this study with median age of 50 years that were selected through convenient sampling method. Most of respondent had internal jugular catheter (78.8%) and the used of TVA in situ was within four to six months. All patients had experienced TVA complication that caused removal of the catheter. Complications of the catheter were catheter associated bloodstream infection 38.5%, catheter thrombosis 36.5% and catheter insufficient blood flow 25%. However, all these complication had no impact on respondents' quality of life. The occurrence of TVA complication among HD patients in this study was I OO%. Further study on larger sample size is required to ratify these findings.